(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
Under cold climatic conditions, when the ground surface freezes, pressurized subsurface water emerges through porous soil layers, forming ice accumulations known as aufeis. While aufeis may cause damage to infrastructure and transportation networks in populated areas, they play a crucial role in maintaining ecological balance by enhancing river flows, preserving soil moisture, and serving as freshwater reservoirs. In recent years, the rising average temperatures have led to significant reductions in permafrost and glacial formations, with corresponding decreases in aufeis coverage. This makes detailed investigation of aufeis impacts on both human systems and natural environments particularly important. This study examines spatial and temporal changes in aufeis distribution within the Selenga River basin between 2021 and 2025. The research area encompasses transboundary regions of Mongolia and Russia along the Selenga River basin. Using Sentinel-2 satellite imagery processed through Google Earth Engine, we analyzed aufeis locations and areal extent by calculating spectral indices including the Normalized Difference Snow Index (NDSI) and Normalized Difference Water Index (NDWI). The results of the study indicate that between 2021 and 2025, a total of 35,988 aufeis formations were recorded, covering a cumulative area of 317,976.25 hectares along the Selenga River basin. The year 2021 recorded the highest extent and number of aufeis formations, with 9,053 formations covering an area of 83,123.82 hectares. However, a gradual decrease in both the number and area of aufeis was observed over the subsequent years, reaching a minimum in 2025, when 4,987 formations were recorded over an area of 41,916.61 hectares. Furthermore, our study examined how climatic factors such as mean average air temperature (MAAT) and precipitation have influenced on the changes in both the area and number of aufeis formations.